2016
DOI: 10.3390/w8090374
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Domestic Water Consumption Trends in the City of Alicante: Exploring the Links between the Housing Bubble, the Types of Housing and the Socio-Economic Factors

Abstract: Abstract:The European Mediterranean coastline has experienced major tourism-related urbanization since 1960. This is a dynamic that has led to increased spending on water consumption for urban and tourism-related uses. The objective of this paper is to define and to analyze how domestic water consumption in the city of Alicante evolved between 2000 and 2013. Real billing figures for individual households were analyzed according to the type of housing and the income level of the occupants. The conclusions drawn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 41 publications
2
55
0
2
Order By: Relevance
“…The study by [2] found that the water consumption per capita in Santa Ponça was 771 l/p/d, and 188 l/p/d in El Toro (near Son Ferrer and with a similar housing typology). However, the values obtained in Santa Ponça are quite similar to the 409 l/p/d obtained for detached houses in expansive low-density developments (with a private garden and a swimming pool) in Alicante, which is a tourist region with similar characteristics [3].…”
Section: Water Consumption In the Three Housing Typologiessupporting
confidence: 77%
See 1 more Smart Citation
“…The study by [2] found that the water consumption per capita in Santa Ponça was 771 l/p/d, and 188 l/p/d in El Toro (near Son Ferrer and with a similar housing typology). However, the values obtained in Santa Ponça are quite similar to the 409 l/p/d obtained for detached houses in expansive low-density developments (with a private garden and a swimming pool) in Alicante, which is a tourist region with similar characteristics [3].…”
Section: Water Consumption In the Three Housing Typologiessupporting
confidence: 77%
“…Therefore, the aggregate data of the residential and floating populations are used to determine the urban water demand in the hydrological plans. It is well known that tourists consume more water than the local population [1][2][3][4]. However, official statistics frequently fail to differentiate this from the domestic water consumption [5], or to take into account the fact that the increasing number of residents and some housing typologies (especially high-income residential houses) increase the pressure on water resources [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In 2007, the length of the network totaled almost 1100 km; at the end of 2013, it had expanded an additional 35 km, while 72 km had been renovated. On the other hand, network efficiency rose from 80.49 percent in 1991 to 90 percent in 2015 [39,40] (see Figure 1). …”
Section: Case Studymentioning
confidence: 99%
“…obeying multiple interrelated causes, such as more efficient water fixtures and appliances; growing consumer awareness; smaller demographic and economic growth; and also the effects of rising prices and taxes, especially among low-income groups [40].…”
Section: Case Studymentioning
confidence: 99%
See 1 more Smart Citation